Kadar beta karoten dan warna kue apem berbahan dari komposit tepung ubi jalar ungu dan tepung jagung: Beta carotene content and color characteristics of apem cake enriched with purple sweet potato and corn flour - Fauziyyah, Salwa Danella Atiqoh; Kurnia, Pramudya; Mustikaningrum, Fitriana (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Purple sweet potato and corn flours are considered promising composite alternatives to rice flour in traditional bakery products due to their higher nutritional value and potential to enhance product appearance. This study aimed to evaluate the effects of a purple sweet potato–corn flour composite on β-carotene content and color characteristics of apem cake, a traditional Indonesian steamed cake. A quantitative experimental design was employed using a Completely Randomized Design (CRD) comprising four treatment formulations with two replications. The analyzed variables included β-carotene concentration and instrumental color values (L*, a*, b*). Data were analyzed using one-way ANOVA followed by Duncan’s Multiple Range Test (DMRT) for post hoc comparisons. The results indicated that formulation B exhibited the highest lightness value (L* = 40.18; p = 0.020), demonstrating a significant improvement in brightness. The a* value (red-green axis) did not differ significantly across treatments (p = 0.090). In contrast, b* values (yellow-blue axis) decreased significantly (p = 0.002), with formulation D showing the lowest value, indicating a shift toward a bluish hue. Notably, formulation D also recorded the highest β-carotene content. The best formulation is D with the b* value of 14,3 and betacaroten at 91.71%.